Pemanfaatan Aplikasi Mobile Learning dalam Meningkatkan Literasi Al-Qur’an Siswa Generasi Z - Solikhin, Solikhin; Winarti, Ika (ILJ: Islamic Learning Journal, 2025)
The development of digital technology has significantly influenced the learning styles of Generation Z, including in the context of Islamic education. This study aims to analyze the utilization of mobile learning applications in improving Qur’anic literacy among students at MTs Al Urwatul Wutsqo Jombang. This research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The findings reveal that the use of mobile learning applications enhances students’ learning motivation, Qur’an reading skills, and understanding of the meaning of Qur’anic verses. Furthermore, mobile learning provides flexibility in terms of time and place, aligning with the characteristics of Generation Z who are highly engaged with technology. This study recommends that Islamic educational institutions further integrate digital technology into Qur’anic learning to address the challenges of the digital era and promote sustainable Qur’anic literacy.